Pengaruh Media Tangga Pintar terhadap Hasil Belajar Matematika pada Materi Penjumlahan Siwa Kelas I di SD Negeri 22 Paus - Oktavia Dhea Brigita; Yuli Budhiarti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to determine the effect of using the Smart Ladder media on students’ mathematics learning outcomes in addition. The data were analyzed using normality tests and the Wilcoxon test with the aid of SPSS software. The results showed that before using the Smart Ladder media, students’ mathematics learning outcomes in addition were in the low category, with an average score of 41.7. After using the Smart Ladder media, learning outcomes increased significantly and reached the high category with an average score of 77.9, and the Wilcoxon test results showed a significance value of 0.000 < 0.05, meaning that Ho was rejected and Ha was accepted. This indicates that the data on the use of the Smart Ladder media has a significant effect on mathematics learning outcomes in addition for first-grade students.